Microbial Food Safety An Introduction - Oyarzabal, Omar A.; Backert, Steffen; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
In this book, some of the most qualified scientists review different food safety topics, ranging from emerging and reemerging foodborne pathogens, food regulations in the USA, food risk analysis and the most important foodborne pathogens based on food commodities. This book provides the reader with the necessary knowledge to understand some of the complexities of food safety. However, anybody with basic knowledge in microbiology will find in this book additional information related to a variety of food safety topics.
I. Microorganisms and Food Contamination -- Emerging and Reemerging Foodborne Pathogens -- Clinical Presentations and Pathogenicity of Foodborne Diseases by Bacteria -- Microbiology Terms Applied to Food Safety -- Methods of Identification of Bacterial Foodborne Pathogens -- Methods to Type Foodborne Pathogens for Epidemiological Studies -- Foodborne Viruses -- II. Safety of Major Food Products -- Safety of Vegetable Products -- Safety of Fruit, Nut, and Berry Products -- Safety of Dairy Products -- Safety of Meat Products -- Safety of Fish and Seafood Products -- III. Risk Analysis, Interventions, and Regulations -- Food Risk Analysis -- Interventions to Inhibit or Inactivate Bacterial Pathogens in Foods -- Food Regulations in the United Sates -- Role of Different Regulatory Agencies in the United States -- IV. List of Other Food Safety Resources -- Food Safety Resources -- Glossary.
Keywords: Chemistry; Microbiology; Food science; Agriculture; Chemistry; Food Science; Chemistry/Food Science, general; Applied Microbiology; Agriculture